2021
DOI: 10.1523/eneuro.0120-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Differential Retinoic Acid Signaling in the Hippocampus of Aged Rats with and without Memory Impairment

Abstract: Retinoic acid (RA), a metabolite of vitamin A, has many physiological functions, and mounting evidence points to important roles in cognition. In vitro experiments indicate that RA is involved in homeostatic synaptic scaling in the hippocampus, which supports overall network stability during learning. It has been previously determined that disrupted RA signaling in the hippocampus causes deterioration of memory, that RA signaling declines with age in brain, and that application of RA rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Loss of GABRQ *‐containing neurons is an indicator of early social–emotional cognitive decline in frontotemporal dementia (Gami‐Patel et al, 2022), IL6R* has been associated with memory domain scores, and Alzheimer's disease pathology (cerebrospinal fluid pTau and Aβ42/40 ratio) (Quillen et al, 2023), and DTNB is an indicator of extent of neuronal injury and inflammation in Alzheimer's disease (Neumann et al, 2022). CYP26B1 is upregulated in the prefrontal cortex (Shibata et al, 2021), and there are links between its catabolism in the hippocampus and poor cognitive outcomes in mice (Wołoszynowska‐Fraser et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Loss of GABRQ *‐containing neurons is an indicator of early social–emotional cognitive decline in frontotemporal dementia (Gami‐Patel et al, 2022), IL6R* has been associated with memory domain scores, and Alzheimer's disease pathology (cerebrospinal fluid pTau and Aβ42/40 ratio) (Quillen et al, 2023), and DTNB is an indicator of extent of neuronal injury and inflammation in Alzheimer's disease (Neumann et al, 2022). CYP26B1 is upregulated in the prefrontal cortex (Shibata et al, 2021), and there are links between its catabolism in the hippocampus and poor cognitive outcomes in mice (Wołoszynowska‐Fraser et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, SEMA5A * has previously been associated with hippocampal volume and performance on cognitive tests ( 85 ). CYP26B1 is upregulated in the prefrontal cortex ( 86 ), and there are links between its catabolism in the hippocampus and poor cognitive outcomes in mice ( 87 ).…”
Section: Resultsmentioning
confidence: 99%
“…GNB5 plays a key role in several neurodevelopmental cognitive disabilities (83,84). CYP26B1 is upregulated in the prefrontal cortex (85), and there are links between its catabolism in the hippocampus and poor cognitive outcomes in mice (86).…”
Section: Associations Between G and Individual Genesmentioning
confidence: 99%
“…The most potent form of vitamin A is the nuclear receptor agonist, retinoic acid. In the hippocampus, a primary region implicated in multiple pathways of cognitive decline 21,22 and early AD, 21 retinoic acid is synthesized locally from retinol 23 . Studies in rodents have shown that retinoic acid induces hippocampal neurogenesis and neuronal differentiation, 24,25 rescues vitamin‐A deficiency‐induced spatial memory impairment, 26,27 and reverses age‐related memory deficits 28,29 .…”
Section: Perspectives Articlementioning
confidence: 99%
“…In the hippocampus, a primary region implicated in multiple pathways of cognitive decline 21,22 and early AD, 21 retinoic acid is synthesized locally from retinol. 23 Studies in rodents have shown that retinoic acid induces hippocampal neurogenesis and neuronal differentiation, 24,25 rescues vitamin-A deficiencyinduced spatial memory impairment, 26,27 and reverses age-related memory deficits. 28,29 Rodent models have also demonstrated that vitamin A deficiency reduces hippocampal volume and plasticity, and increases amyloid-β deposition, as compared to vitamin A replete controls.…”
Section: Perspectives Articlementioning
confidence: 99%